Rehabilitation Guidelines for Use Following a Periacetabular Osteotomy (PAO): A North American Based Delphi Consensus - Ashley E. Disantis; Ethan Ruh; RobRoy Martin; Keelan Enseki; Michael McClincy (North American Sports Medicine Institute, 2022)
# Background Treatment of acetabular dysplasia with a periacetabular osteotomy (PAO) has been shown to improve long term outcomes and is considered the gold standard in the setting of symptomatic hip dysplasia in patients younger than 35 years of age. Post-operative rehabilitation following a PAO plays an important role in helping patients return to their prior level of function and reduce the impact of strength deficits that may persist. Currently, there is a paucity of research supporting post-operative rehabilitation guidelines. The purpose of this study is to present expert-driven rehabilitation guidelines to reduce practice variation following a PAO. # Methods A panel of 16 physiotherapists from across the United States and Canada who were identified as experts in PAO rehabilitation by high-volume hip preservation surgeons participated in this Delphi study. Panelists were presented with 11 questions pertaining to rehabilitation guidelines following a PAO. Three iterative survey rounds were presented to the panelists based on responses to these questions. This three-step Delphi method was utilized to establish consensus on post-operative rehabilitation guidelines following a PAO. # Results Total (100%) participation was achieved for all three survey rounds. Consensus (\>75%) was reached for 11/11 questions pertaining to the following areas: 1) weight-bearing and range of motion (ROM) precautions, 2) therapeutic exercise prescription including neuromuscular control, cardiovascular exercise, and flexibility, and 3) objective measures for return to straight line running and return to full participation in sports. # Conclusion This Delphi study established expert-driven rehabilitation guidelines for use following a PAO. The standardization of rehabilitative care following PAO is essential for achieving optimal outcomes despite other factors such as geographical location and socioeconomic status. Further research on patient-reported outcomes is necessary to confirm successful rehabilitation following the guidelines outlined in this study.